2021
DOI: 10.1101/2021.03.16.435569
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cost efficiency of institutional incentives in finite populations

Abstract: Institutions can provide incentives to increase cooperation behaviour in a population where this behaviour is infrequent. This process is costly, and it is thus important to optimize the overall spending. This problem can be mathematically formulated as a multi-objective optimization problem where one wishes to minimize the cost of providing incentives while ensuring a desired level of cooperation within the population. In this paper, we provide a rigorous analysis for this problem. We study cooperation dil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Indeed, we have shown that the larger the cost of participation ( ) is, the greater fraction of this budget should to be used for encouraging participation to achieve an optimal level of cooperation. This observation confirms the importance of studying incentives in models considering an explicit process of commitment formation, which has been omitted in extant models of institutional incentives (Chen et al, 2015, Duong and Han, 2021, García and Traulsen, 2019, Góis et al, 2019, Wang et al, 2019. These works have not considered commitment-based interactions nor incentives for encouraging participation in the interaction (and its impact on the overall cooperation).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Indeed, we have shown that the larger the cost of participation ( ) is, the greater fraction of this budget should to be used for encouraging participation to achieve an optimal level of cooperation. This observation confirms the importance of studying incentives in models considering an explicit process of commitment formation, which has been omitted in extant models of institutional incentives (Chen et al, 2015, Duong and Han, 2021, García and Traulsen, 2019, Góis et al, 2019, Wang et al, 2019. These works have not considered commitment-based interactions nor incentives for encouraging participation in the interaction (and its impact on the overall cooperation).…”
Section: Discussionmentioning
confidence: 58%
“…However, it might be more costly for the institutions to provide rewards when compliant behaviour is frequent. An interesting direction is to consider how to combine reward and punishment in a cost efficient way, as have been done in the context of social dilemmas (without considering commitment-based behaviours) (Chen et al, 2015, Duong and Han, 2021, Góis et al, 2019, Sasaki et al, 2012, Sun et al, 2021.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the target variable and the model score are unrelated, and we test for each possible set of targets using this unique measure of fairness. Similar to previous works (Chen et al, 2015, Cimpeanu et al, 2019, Duong and Han, 2021a, Wang et al, 2019, we measure cost-efficiency of an interference strategy by its total cost required over time. Furthermore, we will discuss explicitly the requirements for each strategy to be implementable, such as the availability of information about the population and local neighbourhoods, and budget constraints in each time step.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the external decision maker needs to take into consideration that they will have to repeatedly interfere in the system, in order to sustain the desired behaviour over time. Note however that, for simplicity, previous works have either omitted mutation (Han andTran-Thanh, 2018, Wang et al, 2019), or assumed that it is infinitely small (for analytical treatment) Han, 2021a, Han and. Mutation (behavioural exploration), where agents can freely experiment with new behaviours, is usually non-negligible in real populations and has been shown to play an important role in enabling cooperation in the context of social dilemmas (Antal et al, 2009, Duong and Han, 2019, 2021b, Han et al, 2012, Rand et al, 2013.…”
Section: Introductionmentioning
confidence: 99%